THE IMPLEMENTATION OF YOUTUBE IN TEACHING VOCABULARY FOR YOUNG LEARNERS - Hakim, Lystiana Nurhayat (JOURNAL OF ADVANCED ENGLISH STUDIES, 2019)
Vocabulary has become a crucial aspect of learning foreign language. For young learners, the first words that they acquire could be like profound basis for a better learning of children. Related to the importance of vocabulary for young learners the teachers have to provide a new interesting teaching aid such as YouTube. The aim of this study is to find out the the differences between students who are taught by using YouTube and those who are not and to find out students’ perception of using YouTube in teaching vocabulary. This study employed quantitative and qualitative research design. The result of the study showed that the use of YouTube in this study is effective in teaching vocabulary for young learners and students who are taught by using YouTube are master in vocabulary. Furthermore, from the classroom observation and questionnaire, the use of YouTube can motivate students to learn vocabulary and the students have positive perception of using YouTube in teaching vocabulary for young learners